Complete genomes reveal signatures of demographic and genetic declines in the woolly mammoth - Palkopoulou, Eleftheria; Mallick, Swapan; Skoglund, Pontus; Enk, Jacob; Rohland, Nadin; Li, Heng; Omrak, Ayça; Vartanyan, Sergey; Poinar, Hendrik; Götherström, Anders; Reich, David; Dalén, Love (Current biology, 2015)
The processes leading up to species extinctions are typically characterized by prolonged declines in population size and geographic distribution, followed by a phase in which populations are very small and may be subject to intrinsic threats, including loss of genetic diversity and inbreeding. However, whether such genetic factors have had an impact on species prior to their extinction is unclear; examining this would require a detailed reconstruction of a species' demographic history as well as changes in genome-wide diversity leading up to its extinction. Here, we present high-quality complete genome sequences from two woolly mammoths (Mammuthus primigenius). The first mammoth was sequenced at 17.1-fold coverage and dates to ∼4,300 years before present, representing one of the last surviving individuals on Wrangel Island. The second mammoth, sequenced at 11.2-fold coverage, was obtained from an ∼44,800-year-old specimen from the Late Pleistocene population in northeastern Siberia. The demographic trajectories inferred from the two genomes are qualitatively similar and reveal a population bottleneck during the Middle or Early Pleistocene, and a more recent severe decline in the ancestors of the Wrangel mammoth at the end of the last glaciation. A comparison of the two genomes shows that the Wrangel mammoth has a 20% reduction in heterozygosity as well as a 28-fold increase in the fraction of the genome that comprises runs of homozygosity. We conclude that the population on Wrangel Island, which was the last surviving woolly mammoth population, was subject to reduced genetic diversity shortly before it became extinct.